Juridical-Legal Study of the Criminal Policy of Iran Regarding Prejudicial to Public Decency Crimes with an Approach to the Ancient Laws - Rezaeian koochi, Mohammad Reza; Najafzadeh Shavaki, Ghadir; sahragard, mojtaba (Journal of History Culture and Art Research, 2017)
Iranian legislator has never presented a criterion for detecting crimes prejudicial to public decency, but instead of defining prejudicial to public decency crimes, the legislator has only stated prejudicial to public decency crimes. Because main purpose of this study is identifying concept of public decency crimes in the criminal code of Iran and ancient laws, their proper application regarding the changes of new Islamic penal code of Iran and its effectiveness on the decision-making of judges, based on the nature, scope and commentaries, this research studies the type and examples of prejudicial to public decency cries in ancient laws and response to public decency crimes, we will analyze severity and violence of punishment for these crimes. Challenging questions may raise in this regard, such as what is the type and examples of chastity crimes from ancient law view, Imamieh jurisprudence view and legal system of Iran? And how is the approach and response of ancient laws to chastity crimes compared to religious principles and punishment system of Iran's legal system? This research studies the history of chastity crimes in the jurisprudence teachings and identifies crimes prejudicial to public decency in the ancient laws and basis for accepting these crimes in legal system of Iran.